2013
DOI: 10.1063/1.4818872
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular lamellar-in-lamellar and other planar morphologies in A-b-(B-b-A)2-b-C and (B-b-A)2-b-C ternary multiblock copolymer melts

Abstract: Ordered planar morphologies in A-b-(B-b-A)2-b-C and (B-b-A)2-b-C terpolymer melts are studied within the framework of the self-consistent field theory for volume fractions of components A, B, and C in the ratio 1:1:2 and the Flory-Huggins interaction parameters satisfying χ(AB) = 2χ(AC). The stable phases turn out to be the disordered, hexagonal, parallel lamellar-in-lamellar L∥ (including the simple lamellar) as well as non-shifted and shifted (L⊥ and SL⊥) perpendicular lamellar-in-lamellar morphologies. Depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Furthermore, the appearance of L ⊥ can be ascribed to the low A/C interfacial energy, which is consistent with the experimental observation of perpendicular lamellae ,, and SCFT results. ,, Markov and coworkers studied the phase behavior of A­(BC) 2 B multiblock copolymers at fixed volume fraction f A / f B / f C = 2:1:1 . They observed a series of planar nanostructures, including hexagonal, parallel lamellar-in-lamellar, and non-shifted and shifted perpendicular lamellar-in-lamellar nanostructures.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, the appearance of L ⊥ can be ascribed to the low A/C interfacial energy, which is consistent with the experimental observation of perpendicular lamellae ,, and SCFT results. ,, Markov and coworkers studied the phase behavior of A­(BC) 2 B multiblock copolymers at fixed volume fraction f A / f B / f C = 2:1:1 . They observed a series of planar nanostructures, including hexagonal, parallel lamellar-in-lamellar, and non-shifted and shifted perpendicular lamellar-in-lamellar nanostructures.…”
Section: Resultssupporting
confidence: 78%
“…19,23,36 Markov and coworkers studied the phase behavior of A(BC) 2 B multiblock copolymers at fixed volume fraction f A /f B /f C = 2:1:1. 37 They observed a series of planar nanostructures, including hexagonal, parallel lamellar-inlamellar, and non-shifted and shifted perpendicular lamellarin-lamellar nanostructures. To make a comparison with their work, we obtain a phase transition sequence with decreasing χ AB N and χ AC N at fixed f A = 0.5 and χ BC N = 80, which is L 5 → L ⊥ → L 3 → D. This transition sequence is consistent with the phase transition sequence of Markov's work, where they found that the phase transition sequence is…”
Section: Models and Methodsmentioning
confidence: 99%
“…Theory and simulation are of particular use to develop a fundamental understanding of the structure–property relationship of the hierarchical structures. On the aspect of structure studies, self-consistent field (SCFT) theory and dissipative particle dynamics (DPD) simulation have successfully been used to predict the structures and morphologies constituted by the multiblock copolymers. Lin and coauthors have used SCFT and DPD to reproduce a series of hierarchical structures found in the experiments. , On the aspect of property studies, nonequilibrium molecular dynamics (NEMD) simulations are widely utilized to examine the rheological properties of block copolymers. Ganesan et al combined nonequilibrium oscillatory shear technique and DPD simulation to study the viscoelastic properties of ABA triblock copolymers, which can form a gel in solution due to the amphiphilic interactions . They demonstrated that their simulation results show a high coincidence with other theoretical calculations and experimental findings.…”
Section: Introductionmentioning
confidence: 99%
“…This independent tunability in the size of the different lattices, and thereby in the different orientations of the structure, is in contrast with the phase-in-phase nanostructures that were observed in other systems such as linear or mikto-arm multiblock copolymers as well as the supramolecular materials assembled through complexation of mesogenic moieties or hydrogen bonding. In these previously reported materials, two sets of lattice parameters were mutually determined by the overall composition and lengths of all blocks and could not be decoupled from one another [29][30][31][32][33][34] . A (PS78)100-b-(PDMS37-alt-PLA20)100 GBCP was also synthesized with a long backbone extending the d-spacing of superstructure to the mesoscale range (d1 = 105.1 nm), while the substructure (d2 = 10.6 nm) was maintained in the nanoscale range (Fig.…”
mentioning
confidence: 99%